High and Higher: Fertility of Black and White Women with College and Postgraduate Education in the United States - Natalie Nitsche; Hannah Brückner (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2018)
A postponement of first births among college graduates, and increases in childlessness in the US are well documented, as are black-white fertility differentials. However, little is known on how first birth postponement and childlessness differ between women with college and postgraduate education. Likewise, black-white fertility differentials among women with college and post-graduate education, in particular among recent birth cohorts, have not yet been addressed in the literature. We use the CPS Fertility Supplement 1979-2012 to estimate first birth survival functions for black and white women with college and post-graduate education for birth cohorts 1931-1980. Our findings show a significant postponement of the first birth by about 2 years among women with postgraduate education compared to college graduates. Median ages at first birth plateau around age 32-33 for this group. Differentials in childlessness between college graduates and women with postgraduate education are present in the 1940s and 1950s birth cohorts, but disappear for women born after 1960. Furthermore, black highly educated women have significantly more first births early in the life course and higher rates of non-marital fertility than their white counterparts across all birth cohorts. Our findings thus suggest diverging pathways into motherhood between black and white women, even among this most highly educated segment of the population.
Keywords: 300; Fertility; education; race; inequality; childlessness; parenthood; first birth; postgraduate education